Fenomena Guru Rangkap pada Bidang Studi yang Berbeda di SMP Nahdlatul Ulama Kajen Pekalongan - Rachel Amalia, Rachel; Ahmad Ta’rifin, Ahmad; Nikmatul Azizah; Jazuli Ikrom Fadoli; Nadia Rihhadatul Aisy (La-Tahzan: Jurnal Pendidikan Islam, 2024)
A concurrent teacher is an educator who carries out learning by combining several different fields of study, due to a shortage of educators, as well as a lack of school infrastructure. The purpose of this study was to determine the strategies used by educators in managing classroom teachers at NU Kajen Junior High School. The research method used is descriptive qualitative. Data collection techniques used in this research are interviews, observation, documentation and document analysis. The analysis technique used is an interactive analysis model that classifies data into 3 steps, namely, reduction, presentation and conclusion. In this study the author describes the definition of concurrent teachers, how it is implemented, what kind of obstacles experienced by concurrent class teachers to the teacher's efforts in solving these obstacles. The results of the study inform us that multi-grade educators at NU Kajen Junior High School experience a little difficulty, because they teach not in accordance with the field that should be. With this, educators must have strategies for teaching in multi-grade classes, these strategies include: classroom management, collaborative classes, the use of differentiated learning, connecting teaching with real life, and integrating technology in teaching. In carrying out the strategy, a teacher is required to be able to adjust, because in teaching he must understand what he is teaching, especially if it is not in his field, of course it is not something easy.